Bilmeyi Bilmek - Mehmet Tayfun Gülle (Türk Kütüphaneciliği)
The editorial, in the first place, mentions the organization of the 47th Library Week not in the capital city but, for the first time, in the ancient library of Celsus in Ephesus and the acceleration this has caused, and then discusses the possible causes behind the turbulences that first started in North Africa and then spread into the Middle East in 2011. It sets forth the idea that Western intrusion into the domestic affairs of MENA (Middle East and North Africa) countries due to their rich underground resources is the underlining cause behind similar problems ongoing for years and advocates the view that people of the region failed to have a say in the structuring of these countries due to their long-standing dogmas so that authoritarian regimes could survive for years. Under these circumstances, poverty has become continuous in the region despite the underground resources that are abundant. The editorial argues that people of the region have a problem of not knowing How to Know due to causes like being closed to scientific thinking, intolerance towards different works of opinion and art, lack of a culture of discussion, etc. and that this problem can only be solved by considering the concepts of knowing and learning independently of dogmas.